2022
DOI: 10.1002/er.8627
|View full text |Cite
|
Sign up to set email alerts
|

Floating and terrestrial photovoltaic systems comparison under extreme weather conditions

Abstract: Greenhouse gas emissions are primarily caused by the exploitation of fossil fuels as an energy source, and one way to reduce those emissions is to utilize renewable energies such as solar irradiation conversion. In the city of Istanbul, two Floating Photovoltaic (FPV) prototypes were installed in 2016 on Büyükçekmece Lake, a large body of water that supplies fresh water to the city, as a means of both reducing evaporation loss and generating electricity. The systems had capacities of 90 and 30 kWp, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Another approach is to inspect the PV modules regularly to prevent cracks from occurring and to handle the PV properly during all maneuvers and transportation [25]. Finally, it is important to design installations that account for unusual environmental conditions, such as strong winds, to ensure the durability and optimal performance of the PV modules [26].…”
Section: Solar Pv Module Cracks Impact On Pv Output Powermentioning
confidence: 99%
“…Another approach is to inspect the PV modules regularly to prevent cracks from occurring and to handle the PV properly during all maneuvers and transportation [25]. Finally, it is important to design installations that account for unusual environmental conditions, such as strong winds, to ensure the durability and optimal performance of the PV modules [26].…”
Section: Solar Pv Module Cracks Impact On Pv Output Powermentioning
confidence: 99%
“…Kaymak and Sahin [29] compared floating PV power plants and ground-based PV power plants under extreme weather conditions. Based on the measured values of electricity production, it was found that both types of power plants provide equally good results.…”
Section: Introductionmentioning
confidence: 99%
“…FPVs are also highly dependent on careful and well-planned engineering projects due to their exposure to strong winds and harsh waves, especially when installed in their natural environments over water reservoirs (Figure 1), [35,36,[43][44][45][46][47]. However, a comprehensive review of the literature reveals a notable absence of indepth research in this regard.…”
Section: Introductionmentioning
confidence: 99%